2017
DOI: 10.1681/asn.2016080877
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–Mediated Expansion of Type 2 Innate Lymphoid Cells Protects from Progressive Glomerulosclerosis

Abstract: Innate lymphoid cells (ILCs) have an important role in the immune system's response to different forms of infectious and noninfectious pathologies. In particular, IL-5- and IL-13-producing type 2 ILCs (ILC2s) have been implicated in repair mechanisms that restore tissue integrity after injury. However, the presence of renal ILCs in humans has not been reported. In this study, we show that ILC populations are present in the healthy human kidney. A detailed characterization of kidney-residing ILC populations rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 50 publications
(69 reference statements)
5
120
3
Order By: Relevance
“…1B). In other types of innate lymphocytes, IL‐33 can stimulate IL‐5 and IL‐13 expression 19 . In contrast, IL‐33 alone or in combination with IL‐12 had no measurable effect on expression of IL5 or IL13 expression by human NK cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1B). In other types of innate lymphocytes, IL‐33 can stimulate IL‐5 and IL‐13 expression 19 . In contrast, IL‐33 alone or in combination with IL‐12 had no measurable effect on expression of IL5 or IL13 expression by human NK cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…A and B). We recently described ILC2s to be the major ILC subtype residing in the kidney of C57BL/6 and BALB/c mice . Similarly, in MRL control mice, as well as in and young and in diseased MRL‐ lpr mice, almost 80% of total ILCs were characterized as Lin − CD127 + CD25 hi GATA3 + ILC2s.…”
Section: Resultsmentioning
confidence: 97%
“…IL‐33 induced partial protection against the typical features of doxorubicin‐induced nephropathy such as tubular inflammation and fibrotic‐like remodeling . It was demonstrated that these effects occur independently of adaptive immunity using mice deficient in T and B cells ( Rag2 −/− ), and mice deficient in T, B and ILCs ( Rag2 −/− Il2rcg −/− ) . However, it is also possible that non‐ILC, ST2 expressing cells such as basophils, eosinophils and mast cells may have important roles in protection against renal insult .…”
Section: Ilc2s As a Potential Cellular Therapy In Renal Injurymentioning
confidence: 99%